Evaluating the User Experience of Consumer Sleep Technologies with the MALTU mode - Moreira, Francisco; Coutinho, Emanuel; Martins, Marcelo; Feitosa, Carlos (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
Sleep is a vital physiological need for human health and well-being, and its quality plays a crucial role in our daily lives. Inadequate sleep can lead to a range of health problems, including chronic fatigue, lack of concentration, cognitive impairment, and an increased risk of cardiovascular and metabolic diseases. Amidst an increasingly aware society of the benefits of well slept nights, there is a growing interest in monitoring and optimizing sleep. This trend is amplified by the continuous advancement of technology, particularly the increase of the Internet of Things (IoT) and E-Health technologies. In this context, the development of consumer sleep technologies emerges alongside the increasingly easier methods to utilize them and the growing awareness of the importance of sleep for health. These technologies offer a variety of solutions, ranging from mobile applications to smart wearable devices. These tools can empower individuals to take steps to improve their sleep hygiene and, consequently, their quality of life. However, some user reviews on the Google Play platform raises issues related to their user experience across all consumer sleep technologies. This article aims to evaluate the User Experience of consumer sleep technologies based on users reviews on Google Play by using the extended MALTU instrument. The evaluation consists in collecting reviews on the platform to analyse and categorize them with consistency and real user reviews. A bibliographical research about consumer sleep technologies was also carried out. The technologies under evaluation include Oura, a sensor-equipped ring, Whoop, a sensorequipped band and the Sleep as Android app. The results revealed issues regarding interface, synchronization and metrics.